Inclusive linguistic policy in Spain for newly arrived migrant students: Dilemmas and tensions in times of crisis - Rodríguez Izquierdo, Rosa María (Education Policy Analysis Archives, 2018)
This article examines the linguistic policies aimed at students of foreign nationality recently incorporated into the educational system in Spain. First, we provide a description of language support policies and programs at the school level, and in particular of the so-called “special classrooms.” Secondly, we will make a brief analysis of their impact with the intention to contribute to the debate on how they have been able to serve for the development of inclusion processes or for the implementation of forms of exclusion or segregation of these students. The results reveal that in the special classrooms the complex nature of what the learning of the language implies is not recognized, without questioning the school organization. Rather, the measures are based on the notions of compensation and the deficit approach of students of foreign nationality. The article argues that as long as policies are based on such ideas, students of foreign nationality will continue to be at a disadvantage and will have fewer educational opportunities. Finally, a school model that favors linguistic support not only for students of foreign nationality but also as an instrument of quality education for all is proposed.